2022
DOI: 10.3393/ac.2021.00283.0040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of implementing Enhanced Recovery After Surgery protocol in elderly colorectal cancer patients

Abstract: The aim of this study was to evaluate the safety and feasibility of applying enhanced recovery after surgery (ERAS) protocol in elderly colorectal cancer patients. Methods: The medical records of patients who underwent elective colorectal cancer surgery at our institution, from January 2017 to December 2017, were reviewed. Patients were divided into 2 groups: the young group (YG, patients aged 70 and under 70 years) and the old group (OG, patients over 70 years old). Perioperative outcomes and length of hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The authors have previously published papers on ERAS protocol implementation and presented them to the Quality Improvement Society, Colon and Anal Society, Society for Surgical Metabolism and Nutrition, Korean Society for Parenteral and Enteral Nutrition, ERAS Society, and the Society for Surgical Infectious Diseases. These papers included the comparison of inflammation [ 2 ], surgical site infection [ 3 ], and complication types before and after protocol application [ 4 5 ]; comparisons of systemic and technical approaches [ 4 ]; and a comparison of compliance with the ERAS system [ 4 ]. Previous analyses found that applying the protocol decreased the inflammation and shortened the duration of hospital stay, without any difference in the complication rates; moreover, there was adequate postoperative pain control.…”
Section: Methodsmentioning
confidence: 99%
“…The authors have previously published papers on ERAS protocol implementation and presented them to the Quality Improvement Society, Colon and Anal Society, Society for Surgical Metabolism and Nutrition, Korean Society for Parenteral and Enteral Nutrition, ERAS Society, and the Society for Surgical Infectious Diseases. These papers included the comparison of inflammation [ 2 ], surgical site infection [ 3 ], and complication types before and after protocol application [ 4 5 ]; comparisons of systemic and technical approaches [ 4 ]; and a comparison of compliance with the ERAS system [ 4 ]. Previous analyses found that applying the protocol decreased the inflammation and shortened the duration of hospital stay, without any difference in the complication rates; moreover, there was adequate postoperative pain control.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, enhanced recovery after surgery (ERAS) program has shown that early rehab and early feeding in postoperative patients are good prognostic factors for patients' recovery [ 110 111 112 113 114 115 ]. The ERAS program recommends catheter removal on postoperative day 1, but surgeons should be taken care when removing it due to the risk of nerve damage during rectal cancer surgery.…”
Section: How To Improve Surgical Outcomesmentioning
confidence: 99%
“…Additional-ly, one study was conducted in a foreign country and another did not include details about the ERAS protocol, leading to their exclusion. Finally, the remaining 16 studies were analyzed [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Table 1 presents the authorship status of anesthesiologists in these studies, along with the inclusion of ERAS items related to the field of anesthesiology.…”
Section: Current Status Of Eras In South Koreamentioning
confidence: 99%